2014
DOI: 10.1103/physrevstab.17.081002
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of nonlinear observables in the Large Hadron Collider using kicked beams

Abstract: The nonlinear dynamics of a circular accelerator such as the Large Hadron Collider (LHC) may significantly impact its performance. As the LHC progresses to more challenging regimes of operation it is to be expected that the nonlinear single particle dynamics in the transverse planes will play an increasing role in limiting the reach of the accelerator. As such it is vital that the nonlinear sources are well understood. The nonlinear fields of a circular accelerator may be probed through measurement of the ampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 9 publications
1
29
0
Order By: Relevance
“…The actual LHC dynamic aperture at injection was measured with the help of kicked beams [98]. The measured and simulated dynamic aperture values agree well.…”
Section: Dynamic Aperturementioning
confidence: 76%
See 1 more Smart Citation
“…The actual LHC dynamic aperture at injection was measured with the help of kicked beams [98]. The measured and simulated dynamic aperture values agree well.…”
Section: Dynamic Aperturementioning
confidence: 76%
“…The measured and simulated dynamic aperture values agree well. It was also shown that through a minimization of readily observed nonlinear parameters it is possible to increase the LHC dynamic aperture [98].…”
Section: Dynamic Aperturementioning
confidence: 99%
“…Compelling experimental observations in the LHC [5] suggested the existence of an amplitude dependent closest tune approach. These experimental observations have been further complemented with computer simulations of the LHC in [6] identifying the key ingredients to reproduce the observations, namely linear coupling and normal octupole fields.…”
Section: Introductionmentioning
confidence: 99%
“…However, upon reduction of the LHC β Ã from 1 to 0.6 m in 2012, a significant degradation of the beam lifetime was observed [12]. Optics studies at injection [13] and top energy [14] also revealed larger than expected discrepancies between the measured and predicted first and second order amplitude detuning. Nonlinear errors in the triplets and separation dipoles are one of several candidates for the source of these reductions in performance.…”
Section: Introductionmentioning
confidence: 99%